Education of Deported Lithuanian Children - Juodėnaitė, Gabija (Genocidas ir rezistencija, 2021)
As a result of Soviet repression about 40,000 Lithuanian children with their families were deported to Siberia, where they had started or continued their education. The Soviet, with knowledge of education importance of the new regime loyal generation, spend a lot of attention, increased funding, and enforce compulsory education. The education system was affected by World War II: the number of pupils in schools fell by as much as 25%, pre-war levels were reached again by 1950. School conditions were poor – children did not have learning tools, there was a lack of premises, textbooks, teachers. The situation started to get a little better in the postwar period, but no major changes took place until about the early 1960s. Teachers had the greatest influence to the quality of learning. Ideological education played an important role to the learning system turning children into loyal Soviet citizens. However, adults were teaching their children at home in case of possible ideology affection, loss of national identity. The opportunities of deported people to study at higher schools were limited, nevertheless, a number of them entered higher education and completed their studies.
Keywords: Soviet Union; deportees; education; ideological indoctrination